First South American record of the rare ichneumonoid subfamily Masoninae van Achterberg (Hymenoptera: Ichneumonoidea: Ichneumonidae) with description of a new species from Brazil - Quicke, Donald L.j.; Chaul, Júlio Cezar Mário; Butcher, Buntika A. (Zootaxa, 2019)
Masona popeye Quicke & Chaul sp. n. is described from Brazil, and differentiated from other species of the genus. Described extant species of Masona are known from Australia and south eastern U.S.A. (Georgia and Florida including the Key Islands). Two undescribed species are known from Tanzania and Cambodia. The new species is therefore the first representative of the subfamily Masoninae van Achterberg from South America, demonstrating the completely cosmopolitan distribution of this very poorly known group. The new species most closely resembles a fossil species, M. pyriceps van Achterberg, 2001, from Dominican amber with which it shares the plesiomorphic presence of a scutellum.